Combined Spinal Epidural Anesthesia for Total Hip Replacement Surgery in Birendra Army Hospital - KC, NB; Rai, S; Chand, P; Joshi, A; Kunwar, BR (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Total Hip Replacement surgery is one of the most commonly performed surgeries worldwide. Epidural anaesthesia have shown decrease incidence of DVT in these patient. Hence, combined spinal epidural spinal anesthesia is now a preferred technique over spinal anesthesia alone. We have been practicing combined spinal epidural anesthesia routienely in total joint replacement, but have not analyzed the result. The aim of this study was to analyse various aspect of combined spinal epidura anesthesia. Methods: thirteen cases of ASA I and II who underwent Total Hip Arthroplasty under combined spinal epidural anesthesia were analysed. First epidural was given in space L2-3/L3-4 and patency was confirmed with test dose with InjXylocaine 2% with Adrenaline 3 ml, followed by Spinal anesthesia one space below with Bupivacaine 0.5% 3 ml. Results: Intra operative Mean Blood Pressure had dropped up to 55 mm of Hg.To maintain Blood pressure, Intravenous Fluid was given in average is 2423.077 ml and Vasopressure drug (Mephenteramine Maleate) was given in average of14.769 mg. Dura was accidentally puncture in one patient during epidural insertion and two epidural failed to provide post operative analgesia. Post operative rehabilitation was easy, one one patient developed DVT after 4 weeks of surgery. Conclusion: Combined epidural analgesia effectively manages postoperative pain, allows early ambulation and reduces the risk of deep vein thrombosis and thromboembolism, Although significant drop of Blood pressure was noted in all cases. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6447 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 32-36